An intuitive visual interface for a real-time monitoring system for human gait using IMUs - Ribeiro, Nuno Miguel Ferrete (2017)
A Matlab Graphical User Interface (GUI) to help monitor the human gait in real time, and to enable to better understand the information of the used Inertial Measurement Units (IMUs) system is here presented. The interface not only improved the speed of data processing, but also facilitated the interaction between the user and the system, providing a clearer change of variables and information exchange. In order to ensure a clearer and more reliable data processing an algorithmic state machine (ASM) was implemented. Data from sensors can be used to estimate the orientation of each module through the use of a complementary filter (representation achieved in Quaternions and/or Euler angles), based on previous work. Furthermore, in this article it will be presented the list of requirements built initially for the interface creation as well as the Matlab GUI, its functionalities, and its assessments. Results show quality assessment of the developed interface based on an inquiry made in a group with thirty-six participants, and the assessment of the communication protocol.